2019
DOI: 10.21873/invivo.11659
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cerebroplacental Ratio (CPR) With Adverse Perinatal Outcome in Singleton Pregnancies

Abstract: Background/Aim: For many years clinical research has been concerned with doppler sonography as a non-invasive tool for intrauterine fetal status assessment. A new focus is now placed on the measurement of cerebroplacental index (CPR) as a predictor of fetal outcome. Our aim was to investigate the relationship between the cerebroplacental ratio (CPR), the delivery mode and the fetal outcome in singleton pregnancies. Patients and Methods: A retrospective cohort study of pregnancies in which doppler sonography of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
10
1
1
Order By: Relevance
“…In another study conducted by Grutnner et al, the comparison of patients with spontaneous delivery versus operative delivery showed no significant difference in the cerebroplacental index (p=0.616). 24 In a similar study by Dall'Asta et al, which was a prospective multicenter observational study conducted at three tertiary centers, the study concluded that, while reduced CPR is associated with a higher risk of obstetric intervention due to fetal distress and composite adverse perinatal outcome, it is a poor predictor of adverse perinatal outcome, indicating that there is no significant correlation between the mode of delivery and CPR. 25 However, it must be stressed that in all these studies, even though the mode of delivery has no statistical significance in relation to CPR, LSCS was the most common mode of delivery when taking into account that babies with CPR<1 are more likely to undergo fetal distress when subject to the stress of normal delivery, especially when the time to delivery is prolonged.…”
Section: Discussionmentioning
confidence: 96%
“…In another study conducted by Grutnner et al, the comparison of patients with spontaneous delivery versus operative delivery showed no significant difference in the cerebroplacental index (p=0.616). 24 In a similar study by Dall'Asta et al, which was a prospective multicenter observational study conducted at three tertiary centers, the study concluded that, while reduced CPR is associated with a higher risk of obstetric intervention due to fetal distress and composite adverse perinatal outcome, it is a poor predictor of adverse perinatal outcome, indicating that there is no significant correlation between the mode of delivery and CPR. 25 However, it must be stressed that in all these studies, even though the mode of delivery has no statistical significance in relation to CPR, LSCS was the most common mode of delivery when taking into account that babies with CPR<1 are more likely to undergo fetal distress when subject to the stress of normal delivery, especially when the time to delivery is prolonged.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Ganju, 2020 [19] reported that abnormal CPR is significantly associated with caesarean delivery (p value=0.001). Gruettner and his co-workers, 2019 [13] found that in their cases 41.2% of the patients had a spontaneous delivery, whereas 9.6% had a vaginal operative delivery and 49.3% underwent a cesarean section. When they compared all three types of delivery mode of patients with pathological and normal CPR the difference was significant (p<0.001).…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with our result Ghosh et al, 2018 [11] and Askar et al, 2018 [12] found that there was no statistically significant difference in Doppler parameter as regard gestational age. Gruettner et al, 2019 [13] found that the mean gestational week of delivery was 37 in the group of patients with pathological CPR and 39 in the group of patients with normal CPR. According to their studies, there was a significant difference between the two CPR groups, according to the gestational week at birth (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Pathologies on Doppler ultrasound (maternal, fetoplacental or fetal) correlate with less favourable perinatal outcome 27 , 31 , 32 . 15 – 20% of cases with late-onset FGR exhibit abnormal cerebral perfusion – with unremarkable blood flow in the umbilical cord; by determining the cerebroplacental ratio (CPR) fetuses (with and without growth problems) at increased risk of unfavourable perinatal outcome can be detected more easily 33 , 34 , 35 . The combination of biometry, uterine Doppler ultrasound and CPR in the third trimester can detect the majority of fetuses with a high risk of intrauterine fetal death (IUFT) 31 , but appears to be of little help in detecting SGA/FGR in non-selected populations 36 .…”
Section: Screening Prediction and Preventionmentioning
confidence: 99%
“…Dopplersonografische Auffälligkeiten (maternal, fetoplazentar oder fetal) sind mit einem ungünstigeren perinatalen Outcome assoziiert 27 , 31 , 32 . 15 – 20% der späten FGR zeigen – bei unauffälligem Blutfluss in der Nabelschnur – Auffälligkeiten der zerebralen Perfusion; durch die Bestimmung der zerebroplazentaren Ratio (CPR) können Feten (mit und ohne Wachstumsproblematik) mit einem erhöhten Risiko für ein ungünstiges perinatales Outcome besser detektiert werden 33 , 34 , 35 . Die Kombination Biometrie, uteriner Doppler und CPR im 3.…”
Section: Screening Prädiktion Und Präventionunclassified